A PKC-MARCKS-PI3K regulatory module links Ca2+ and PIP3 signals at the leading edge of polarized macrophages. - Brian P Ziemba; Joseph J Falke (PLoS ONE, 2018)
The leukocyte chemosensory pathway detects attractant gradients and directs cell migration to sites of inflammation, infection, tissue damage, and carcinogenesis. Previous studies have revealed that local Ca2+ and PIP3 signals at the leading edge of polarized leukocytes play central roles in positive feedback loop essential to cell polarization and chemotaxis. These prior studies showed that stimulation of the leading edge Ca2+ signal can strongly activate PI3K, thereby triggering a larger PIP3 signal, but did not elucidate the mechanistic link between Ca2+ and PIP3 signaling. A hypothesis explaining this link emerged, postulating that Ca2+-activated PKC displaces the MARCKS protein from plasma membrane PIP2, thereby releasing sequestered PIP2 to serve as the target and substrate lipid of PI3K in PIP3 production. In vitro single molecule studies of the reconstituted pathway on lipid bilayers demonstrated the feasibility of this PKC-MARCKS-PI3K regulatory module linking Ca2+ and PIP3 signals in the reconstituted system. The present study tests the model predictions in live macrophages by quantifying the effects of: (a) two pathway activators-PDGF and ATP that stimulate chemoreceptors and Ca2+ influx, respectively; and (b) three pathway inhibitors-wortmannin, EGTA, and Go6976 that inhibit PI3K, Ca2+ influx, and PKC, respectively; on (c) four leading edge activity sensors-AKT-PH-mRFP, CKAR, MARCKSp-mRFP, and leading edge area that report on PIP3 density, PKC activity, MARCKS membrane binding, and leading edge expansion/contraction, respectively. The results provide additional evidence that PKC and PI3K are both essential elements of the leading edge positive feedback loop, and strongly support the existence of a PKC-MARCKS-PI3K regulatory module linking the leading edge Ca2+ and PIP3 signals. As predicted, activators stimulate leading edge PKC activity, displacement of MARCKS from the leading edge membrane and increased leading edge PIP3 levels, while inhibitors trigger the opposite effects. Comparison of the findings for the ameboid chemotaxis of leukocytes with recently published findings for the mesenchymal chemotaxis of fibroblasts suggests that some features of the emerging leukocyte leading edge core pathway (PLC-DAG-Ca2+-PKC-MARCKS-PIP2-PI3K-PIP3) may well be shared by all chemotaxing eukaryotic cells, while other elements of the leukocyte pathway may be specialized features of these highly optimized, professional gradient-seeking cells. More broadly, the findings suggest a molecular mechanism for the strong links between phospho-MARCKS and many human cancers.